![\sin(x - \pi) = \sin(x) \cos(\pi) - sin(\pi) \cos(x)](https://tex.z-dn.net/?f=%20%5Csin%28x%20-%20%5Cpi%29%20%3D%20%5Csin%28x%29%20%5Ccos%28%5Cpi%29%20-%20sin%28%5Cpi%29%20%5Ccos%28x%29%20)
via the angle sum formula of sin
![since \: cos(\pi) = - 1 \: and \: sin(\pi) = 0 \: then \\ sin(x - \pi) = - sin(x) \: which \: proves \: the \: first \: choice](https://tex.z-dn.net/?f=since%20%5C%3A%20cos%28%5Cpi%29%20%3D%20-%201%20%5C%3A%20and%20%5C%3A%20sin%28%5Cpi%29%20%3D%200%20%5C%3A%20then%20%5C%5C%20sin%28x%20-%20%5Cpi%29%20%3D%20-%20sin%28x%29%20%5C%3A%20which%20%5C%3A%20proves%20%5C%3A%20the%20%5C%3A%20first%20%5C%3A%20choice)
![\cos(x + y) + cos(x - y) = 2 \cos(x) \cos(y) =\:cos(x + y) + cos(x - y)=cos(x) cos(y)-sin(x)sin(y) +cos(x)cos(y)+sin(x)sin(y)=2cos(x)cos(y)](https://tex.z-dn.net/?f=%20%5Ccos%28x%20%2B%20y%29%20%2B%20cos%28x%20-%20y%29%20%3D%202%20%5Ccos%28x%29%20%5Ccos%28y%29%20%3D%5C%3Acos%28x%20%2B%20y%29%20%2B%20cos%28x%20-%20y%29%3Dcos%28x%29%20cos%28y%29-sin%28x%29sin%28y%29%20%2Bcos%28x%29cos%28y%29%2Bsin%28x%29sin%28y%29%3D2cos%28x%29cos%28y%29)
which proves the second choice
the third choice is wrong since for x=0,y=0 it will show that 2=1 which is incorrect
for the fourth one you can do some thing similar to choice one just expand the sum formula of sin and that should be true too
so
the first , the second and the fourth are all true
Step-by-step explanation:
16x²y⁵16x²y⁵ is the answer
<h2>Mark me BRAINLIEST pls!</h2>
D/2 + c/3
10/2 + 6/3
5+6/3
=5+2
=7
B because 10p means 10 × p